Modified 'Cul-De-Sac' approach for management of a large perforation during maxillary sinus elevation- (A case report) - Yazad Gandhi; Mohit Kheur (Elsevier, 2020)
Dental implants have been in used as a successful mode of rehabilitation of lost dentition for over three decades. Science and techniques have undergone significant progress with time and clinical situations that were deemed unfit for insertion of dental implants due to lack of sufficient bone are now being treated using implants with predictable long term results. Clinicians can now rehabilitate the posterior maxilla with a wide variety of implant-based solutions.There are complications associated with this procedure which may be attributed to diagnostics or the surgical protocol itself and a multitude of management approaches have been suggested in the literature.This report elucidates one such case of management of a large perforation in the Schnederian membrane during elevation using a staged approach.